Revision Surgery to Improve Cosmesis with Immediate Implant-Based Breast Reconstruction. (September 2021) - Clough, R; Darragh, L; Maclennan, L; O'Donoghue, JM
Summary: Background: Following mastectomy for breast cancer, patients may be presented with a range of reconstructive options. The most popular being immediate implant-based reconstruction (IBR). Objective: To determine the rate of revision surgery to improve cosmesis following IBR. Design: Retrospective cohort study. Setting/Patients: All patients who underwent IBR at a single UK-based specialist breast reconstructive centre between June 2012 and June 2013. Measurements: The authors collected data, including demographics, original surgery, revision surgeries and factors likely to influence the cosmetic result. Results: A total of 88 procedures were included in the study and follow up was performed for a mean duration of 1125 days. In all, 39 breasts required further revision to improve cosmesis to undergo a total of 53 additional procedures. Lipomodelling was the most frequently performed revision (n = 18), whilst implant exchange (n = 16), implant removal (n = 11) and other minor revisions (n = 8) made up the remainder. An early (<3 months) complication, adjuvant radiotherapy and capsular contracture significantly increased the chance of revision surgery (p = 0.018, p = 0.04 and p = 0.009, respectively). Revision surgery added an additional monetary cost of 27.1%-74.1%, which depends on the original procedure performed. Limitations: The risk of further revision surgery is likely to be higher in those who are followed up for longer periods. Conclusions: Following immediate IBR, revision surgery represents a substantial burden to the patient including healthcare costs.